2021 26th International Computer Conference, Computer Society of Iran (CSICC) 2021
DOI: 10.1109/csicc52343.2021.9420547
|View full text |Cite
|
Sign up to set email alerts
|

Topology-Aware Graph Signal Sampling for Pooling in Graph Neural Networks

Abstract: Evolving networks are complex data structures that emerge in a wide range of systems in science and engineering. Learning expressive representations for such networks that encode their structural connectivity and temporal evolution is essential for downstream data analytics and machine learning applications. In this study, we introduce a self-supervised method for learning representations of temporal networks and employ these representations in the dynamic link prediction task. While temporal networks are typi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…SAGPool [26] leverages a self-attention graph pooling layer based on hierarchical graph pooling, which can learn hierarchical representation in an end-to-end manner with relatively few parameters. Recent advanced graph neural networks also include EdgePool [27], TopKPool [25], ASAPool [28], MEWISPool [29], GPS [30]. The well-known over-smooth problem prevents the layers of GNNs from going deeper.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…SAGPool [26] leverages a self-attention graph pooling layer based on hierarchical graph pooling, which can learn hierarchical representation in an end-to-end manner with relatively few parameters. Recent advanced graph neural networks also include EdgePool [27], TopKPool [25], ASAPool [28], MEWISPool [29], GPS [30]. The well-known over-smooth problem prevents the layers of GNNs from going deeper.…”
Section: Related Workmentioning
confidence: 99%
“…MEWISPool [29]: A graph pooling method based on maximizing mutual information between the pooled graph and the input graph. It employs the Shannon capacity of the graph as an inductive bias during the pooling process.…”
Section: Baselinesmentioning
confidence: 99%
See 1 more Smart Citation
“…GNNs utilize graph-based pooling techniques to learn hierarchical representations of the input graphs. In a general perspective, one can categorize the graph pooling techniques into the methods which are based on node selection [18,33,34,39], and the methods based on graph coarsening [64,7,52,19,65]. The node-selection-based pooling methods assign an importance score to each node of the graph and select the high score nodes as the pooled nodes.…”
Section: Related Workmentioning
confidence: 99%
“…Graph Neural Networks (GNNs) (Kipf andWelling 2016, 2017) are adept at converting unstructured data into lowdimensional representations by effectively capturing both node features and topological dependencies. The GNN learning tasks broadly focused on node classification, link prediction, and graph classification (You et al 2021;Wang et al 2021), which have demonstrated their effectiveness in various fields such as protein-to-protein interaction (Nouranizadeh et al 2021), molecular medicine (Li et al 2022b) information retrieval (Chen et al 2022), etc. This paper focuses on graph classification, a graph-level task that aims to learn a graph representation with GNNs to predict the graph labels.…”
Section: Introductionmentioning
confidence: 99%